Analysis on the behavior of line differential protective relaying with solar PV penetration - M. E. Yusoff; H. Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Power System Protection is very important in electrical power system as it minimizes power supply interruption to customers, and also prevents damages to electrical equipment.  Lately, renewable energy (RE) penetration in power system helps to support and fulfil the increasing demand of electricity to customers. However, the contribution of power from RE such as solar photovoltaic (PV) will increase the fault level and lead to reverse power flow; thus, it will affect power system protection reliability. This paper focuses on evaluating the reliability of differential protection relay during steady state, internal and external faults conditions when the power system is without and with solar PV penetration. Steady state and three-phase symmetrical line fault will be simulated in IEEE 39 bus test system using power system simulation for engineering (PSS®E) software.